2016
DOI: 10.1159/000447742
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Nerve Conduction Parameters in Proximally and Distally Located Muscles Innervated by the Bundles of Median and Ulnar Nerves

Abstract: Objective: The aim of this study was to investigate and compare the conduction parameters of nerve bundles of median and ulnar nerves that innervate proximal and distal muscles. Subjects and Methods: Thirty male and 30 female healthy volunteers between 18 and 70 years of age were enrolled in the study. The conduction parameters were recorded from the proximally located flexor carpi ulnaris, pronator teres and the flexor carpi radialis muscles to the distally located abductor digiti minimi and abductor pollicis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…When the minimum latencies of the F-wave recorded from the distal and proximal muscles in the lower and upper extremities were compared, it was found that the minimum latencies of the Fwave recorded from the proximal muscles (FUP and FPP) were longer than the minimum F-wave latencies recorded from the distal muscles (FUD and FPD). In previous studies comparing nerve conduction velocities, conduction velocity was found to be higher in proximal muscles with greater mass then the distal small muscles even they are innervated by the same nerve [6,12,13]. Considering the physiology of the Fwave, it is conceivable that the F-wave latency recorded from the proximal muscle should be shorter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When the minimum latencies of the F-wave recorded from the distal and proximal muscles in the lower and upper extremities were compared, it was found that the minimum latencies of the Fwave recorded from the proximal muscles (FUP and FPP) were longer than the minimum F-wave latencies recorded from the distal muscles (FUD and FPD). In previous studies comparing nerve conduction velocities, conduction velocity was found to be higher in proximal muscles with greater mass then the distal small muscles even they are innervated by the same nerve [6,12,13]. Considering the physiology of the Fwave, it is conceivable that the F-wave latency recorded from the proximal muscle should be shorter.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to the distance of the recording electrodes from the muscle due to the excess of subcutaneous tissues in the proximal large mass muscles. One reason for this difference may be that the proximal relatively large mass muscles have higher desynchronization and temporal dispersions, which contain muscle fibers of different nerve conduction diameters [12,14,15]. Previous F-wave studies found that F-wave minimum latency increased with age by 0.03 ms/year in the upper extremity and 0.1 ms/year in the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented that the diameter of the peripheral motor nerve gradually decreases until it reaches the target muscle. (16) The mentioned reference value might be inaccurate in the distal segment.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports describing previous studies stressed that conduction velocities could change along the nerve . Therefore, we analyzed CVD using distal stimulus at the wrist and proximal stimulus at the level of the elbow (conduction along the forearm) in both nerves so that we could eliminate the influence of the conduction velocity slowing within the carpal and Guyon tunnels as well as changes in conduction velocity because of different levels of stimulations.…”
Section: Discussionmentioning
confidence: 99%